PERANCANGAN CORPORATE IDENTITY BALI PAINTBALL ARENA SEBAGAI UPAYA MENGENALKAN PRODUK KEPADA MASYARAKAT - Prayuda, Hendrikus Rian; Bahruddin, Muh; Riqqoh, Abdullah Khoir (Jurnal ArtNouveau, 2014)
Corporate identity is very important in imaging the purposes and objectives of a corporation. Inconsistenct state of corporate Visual identity can cause less familiar the company in society This is happens at Bali Paintball Arena wich is inconsistent in Visual identity so as to make people of Bali are not aware of this company. The problem is considered important because, Bali Paintball Arena is one of the tourist provider the adrenaline in the dewataÂ island always visited by local and foreign tourists. Therefore, it takes a corporate visual identity being inconsistent and it can represent the company of Bali Paintball Arena as the company this can be easily recognizable visually by the local tourists and internationally. By way of issue and designed a visual corporate identity that can answer the needs of Bali Paintball Arena in introducing brand or corporate identity a company to the public at large.